Factors that affecting academic performance among undergraduate students at UUM / Amir Husaini Ahmad@Hamid and Wan Muhammad Idham Wan Ab Rahman - Ahmad@Hamid, Amir Husaini; Wan Ab Rahman, Wan Muhammad Idham (2019)
Education is one of the most important elements in our life. From the education, one can gain new knowledge and that knowledge can be used for personal use and for other use. Education system exist for hundred years ago whereas the education system firstly applied towards the children where they educated themselves through self-directed play and exploration. Knowledge that they obtain can be used for the future purpose and for the use of public to enhance their lifestyle. Education nowadays are important in applying the job opportunities. Education also acts as the level of intelligent of the person where the more knowledge the person has, the more the opportunity for these people to get the job opportunity etc. This principle of this study is to analyse the factors that affecting academic performance among the undergraduate students at UUM. This helps to increase a better understanding on the factors that affecting academic performance among university students. In current condition, education system nowadays use the technological approach such as online learning and virtual learning. Thus, this study to investigate the several factors such as attendance in class, learning facilities, student behaviour and self-assessment.